Socio-Economic Vulnerability of Coastal Communities in Geospatial Aspects Toward Tanjung Carat Port Establishment (Case Study of Sungsang Village, Banyuasin II) - Herda Sabriyah Dara Kospa; Hala Haidir; Al Shida Natul (Jurnal Ilmu Lingkungan, 2025)
The establishment of an international port at Tanjung Carat is part of the National Strategic Projects initiated by the South Sumatra Provincial Government to boost local economic growth. However, the development of the port will involve converting a 60-hectare mangrove forest and imposing restrictions on fishing areas near the port. This will have a negative impact on the socio-economic conditions of the coastal communities in Sungsang Villages, as they heavily depend on marine catches. Therefore, it is essential to analyze and map the socio-economic vulnerabilities of the village community in order to minimize and prevent adverse impacts. This study aims to investigate the level of socio-economic vulnerability of the coastal community to the development of Tanjung Carat port and to provide policy directives as mitigation strategies. The research utilized the ArcGIS Software to weight selected social and economic indicators and convert them into raster data. The Spatial Multi-Criteria Evaluation (SMCE) method was applied to produce social, economic, and socio-economic vulnerability maps, and policy directives were formulated using descriptive analysis. The results revealed that the total socio-economic vulnerability in the four villages falls into the highly vulnerable category, mainly due to the predominant profession as traditional fishermen with relatively low income and education. Formulating policy directives based on applicable regulations in various aspects could be an initial effort to reduce the socio-economic vulnerability. Furthermore, applicable programs are needed to help restore the economy of the impacted fishermen.